Establishment of a highly sensitive and specific exon-trapping system. - Hamaguchi, M (1992)
We have established a highly sensitive and specific exon-trapping system (SETS) with a specific plasmid vector in which an exon in a given DNA segment is identified by its ability to remain as a mature mRNA after splicing. The SETS provides us with the isolation of possible exons rapidly and easily from DNA fragments in chromosomal regions of more than 300 kilobase pairs. Genomic DNA fragments were partially digested and subsequently cloned into plasmid pMHC2, an exon-trapping vector we have constructed. These constructs were transfected into COS-7 cells, and consequent RNA transcripts were spliced in the cells. The resulting mature mRNA was harvested and amplified by using reverse transcription-PCR. Possible exons can be recognized by the sizes of PCR products and cloned into a plasmid vector. The SETS provides a direct means of cloning exons from genomic DNA of more than 300 kilobase pairs within a short period of time. Using this system, we have screened 300-kilobase-pair genomic DNA segments derived from human chromosome 11q13. Human chromosome 11q13 may contain genes responsible for human cancers, because DNA amplification is observed in several malignant tumors. We have successfully identified exon 2 of the HST1 gene and additional transcribed sequences.